2014
DOI: 10.1680/bren.13.00011
|View full text |Cite
|
Sign up to set email alerts
|

Structural monitoring for asset management of railway bridges

Abstract: This paper demonstrates the advantages of site monitoring to aid modelling of the existing condition of a railway bridge with structural problems and to assess the current structure and future remediation. The authors undertook monitoring and assessment on a major 28-span post-tensioned prestressed concrete box-girder bridge on a strategically important railway line in India. The bridge exhibited significant longitudinal web cracking, which restricted its load-carrying capacity to relatively light urban passen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Nevertheless, there is continuing interest in their use in a wide variety of structures (e.g. Kister et al, 2007, Thakur et al, 2011, Banerji et al, 2014, Bravo et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is continuing interest in their use in a wide variety of structures (e.g. Kister et al, 2007, Thakur et al, 2011, Banerji et al, 2014, Bravo et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that with composite materials, sensors can be easily embedded during the manufacturing process and they have, for example, been used successfully by some of the authors for the monitoring of innovative composite bridge structures [1]. In many cases, cheaper conventional sensors such as piezoelectric accelerometers, strain gages or thermocouples can be employed if the monitoring conditions suit, although there are a number of specialist areas where this is not the case and optical fiber methods are to be preferred [2,3]. For metals, however, it can be a real challenge to incorporate sensors effectively: the manufacturing process operates at high temperatures and applications often include harsh environments, which conventional sensors are not easily able to withstand.…”
Section: Introductionmentioning
confidence: 99%
“…In most current applications, usually FOS are glued on the surface of metals, as typically is done in the monitoring of bridges and reinforcement bars [3] but the long-term degradation of adhesives and glues can affect the measurand, often then inducing unexpected errors, for example those caused by a decrease in the strain transfer as the adhesion weakens. Embedding FOS into metallic structures can avoid these problems (and the consequent resultant errors) and thus the challenge of creating a satisfactory and reproducible way to do this must be tackled.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, data acquired by these systems can be used to devise strategies to reduce operational and maintenance costs, improve performance and quality, validate structural solutions, and develop more efficient designs and construction processes for future projects. For example, monitoring systems have been used to support the numerical modelling of existing bridges to aid in assessing current conditions (Banerji et al, 2014).…”
Section: Introductionmentioning
confidence: 99%